Motivasi, Pencapaian Tujuan, Kecemasan, dan Efikasi Diri Dalam Belajar Advance English Terhadap Hasil Belajar Bahasa Inggris (TOEIC Score) Di Politeknik Penerbangan Surabaya - Maharani Sukma, Meita; Fatmawati; Rochmawati, Laila; Margolang, Julfansyah (Politeknik Penerbangan Indonesia Curug, 2023)
This study focuses on exploring motivational reasons for learning English (eg, due to interest/pleasure, pressure from others, or future career goals). To find motivational reasons for learning English, I used the theory of determination (SDT) by Deci and Ryan (1985) as my theoretical framework. Based on the TOEIC score, the results of the cluster analysis showed four different groups, namely the following classifications: intermediate with a toeic score of 405-600, basic working proficiency with a toeic score of 605-780, advanced working abilities with a toeic score with a toeic score of 785-900, general professional proficiency with a toeic score of 905-990. Reasons for motivation to learn English, their goals (i.e., mastery approach goals, mastery-avoidance goals, performance approach goals, and performance avoidance goals), specific foreign language anxiety (i.e., listening, listening, and speaking), and foreign language in general Self Efficacy. Two sets of MANOVA, with follow-up comparison-ANOVA, were used to explain the motivations of different groups regarding foreign language goals and objectives. One ANOVA was used to determine differences in general foreign language self-efficacy. The results showed significant influence and differences between cadets in the four groups based on TOEIC scores on learning motivation, their goals, foreign languages, and foreign languages in general.